2016
DOI: 10.1186/s13229-016-0073-0
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the ‘female camouflage effect’ in autism using a computerized ADOS-2 and a test of sex/gender differences

Abstract: BackgroundAutism spectrum conditions (autism) are diagnosed more frequently in boys than in girls. Females with autism may have been under-identified due to not only a male-biased understanding of autism but also females’ camouflaging. The study describes a new technique that allows automated coding of non-verbal mode of communication (gestures) and offers the possibility of objective, evaluation of gestures, independent of human judgment. The EyesWeb software platform and the Kinect sensor during two demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
185
3
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(209 citation statements)
references
References 32 publications
13
185
3
8
Order By: Relevance
“…This limits the generalizability of results to the wider general population, and possibly to those with ASC. However, recent research has indicated that ASC may be under‐diagnosed in females [Rynkiewicz et al, ; Rutherford et al, ], and that females diagnosed with ASC, without co‐morbid intellectual disability, are at higher risk of dying by suicide than males [Hirvikoski et al, ]. Hence, it is important to explore associations between autistic traits and suicidality in females, without intellectual disability as this is particularly high‐risk group for death by suicide in the ASC population.…”
Section: Discussionmentioning
confidence: 99%
“…This limits the generalizability of results to the wider general population, and possibly to those with ASC. However, recent research has indicated that ASC may be under‐diagnosed in females [Rynkiewicz et al, ; Rutherford et al, ], and that females diagnosed with ASC, without co‐morbid intellectual disability, are at higher risk of dying by suicide than males [Hirvikoski et al, ]. Hence, it is important to explore associations between autistic traits and suicidality in females, without intellectual disability as this is particularly high‐risk group for death by suicide in the ASC population.…”
Section: Discussionmentioning
confidence: 99%
“…Males are more likely to act out in classrooms, which makes them more likely to receive attention, diagnoses, and treatment [17,172,209]. In addition, females with ASD are more likely to camouflage their symptoms and perceive them differently [188,194,210216]. Most accepted knowledge of ASD phenotypes and diagnostic criteria is based on research on primarily male subjects, which can make diagnosis in females more difficult.…”
Section: Are Sex Differences In Autism Overstated?: Possible Underdiamentioning
confidence: 99%
“…Boys are diagnosed with ASD 4-5 times more frequently than girls but the origins of the male prevalence remain incompletely understood (1-7). Equally mysterious but equally compelling is the accumulating evidence that inflammation may contribute to or be a consequence of ASD (8-12).…”
mentioning
confidence: 99%